(untitled) (ModaPalavra e-periódico, 2018)
The use of programming languages in the development of design process brings a new perspective to the methods. It opens opportunities for the designer to go beyond creation and drawing, attending the needs of the project through parameters stablished on a computer environment, generating solutions for the project. Furthermore, generative systems principles can be significantly expressive to integrating the design process and generating creative tools that evolve the limits of imagination with dynamic and customized solutions. The generative modeling considers programming knowledge for the conception of shape through geometric approaches aligned with complex systems that exhibit emergence and self-organization properties. On this scenario, this paper present and discuss the relationship with parametric and generative design for printed textile surfaces. As output, it is presented guidelines identifying how this field could improve with the new methods, and evolve its artistic practices for the creation of fashion products.